Physical training improves motor performance in people with dementia: a randomized controlled trial - Hauer, Klaus; Schwenk, Michael; Zieschang, Tania; Essig, Marco; Oster, Peter (Journal of the American Geriatrics Society, 2012)
Objectives To determine whether a specific, standardized training regimen can improve muscle strength and physical functioning in people with dementia. Design Double-blinded, randomized, controlled trial with 3-month intervention and 3-month follow-up period in 2006 to 2009. Setting Outpatient geriatric rehabilitation. Participants Individuals with confirmed mild to moderate dementia, no severe somatic or psychological disease, and ability to walk 10 m. Most participants were still living independently with or without supportive care. Intervention Supervised, progressive resistance and functional group training for 3 months specifically developed for people with dementia (intervention, n = 62) compared with a low-intensity motor placebo activity (control, n = 60). Measurements Primary outcome measures were one-repetition maximum in a leg press device for maximal strength and duration of the five-chair-stand test for functional performance. Secondary outcome measures were assessed for a number of established parameters for maximal strength, physical function, and physical activity. Results Training significantly improved both primary outcomes (percentage change from baseline: maximal strength, intervention group (IG): +51.5 ± 41.5 kg vs control group (CG): -1.0 ± 28.9 kg, P < .001; functional performance, IG: -25.9 ± 15.1 seconds vs CG: +11.3 ± 60.4 seconds, P < .001). Secondary analysis confirmed effects for all strength and functional parameters. Training gains were partly sustained during follow-up. Low baseline performance on motor tasks but not cognitive impairment predicted positive training response. Physical activity increased significantly during the intervention (P < .001). Conclusion The intensive, dementia-adjusted training was feasible and substantially improved motor performance in frail, older people with dementia and may represent a model for structured rehabilitation or outpatient training.